1949
DOI: 10.1021/ac60035a002
|View full text |Cite
|
Sign up to set email alerts
|

Role of Organic Reagents in Chemistry of Specific, Selective, and Sensitive Reactions

Abstract: The chemistry of specific, selective, and sensitive reactions has the following two tasks as its main objectives: (1) the gathering and classification of, and commenting on, experimental findings which are connected, either directly or indirectly, with the specificity, selectivity, and sensitivity of analytical methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
7

Year Published

1951
1951
2004
2004

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 63 publications
0
59
0
7
Order By: Relevance
“…Reapareceu em "Der Grosse Brockhaus" 6 , no capí-tulo de "Analytisch Chemie". E ele o explicou em detalhe, em seu livro "Specific, Selective and Specific Reactions" (o simplificadamente designado SSS) 7 . A aplicação da química dos complexos de coordenação -introduzida por A. Werner, em 1893 -ao mascaramento e desmascaramento, a fim de obter uma melhora na seletividade de reações químicas não somente foi pioneira 8 , mas ele se tornou altamente especializado, um dos maiores conhecedores da funcionalidade analí-tica em compostos orgânicos, conforme o demonstrou no capítulo de mascaramento, no seu livro SSS e igualmente em duas publicações sobre a correlação dos grupamentos atômicos e a afinidade quí-mica 9,10 .…”
Section: Mascaramento E Desmascaramento Em Química -Seletividade Em Qunclassified
“…Reapareceu em "Der Grosse Brockhaus" 6 , no capí-tulo de "Analytisch Chemie". E ele o explicou em detalhe, em seu livro "Specific, Selective and Specific Reactions" (o simplificadamente designado SSS) 7 . A aplicação da química dos complexos de coordenação -introduzida por A. Werner, em 1893 -ao mascaramento e desmascaramento, a fim de obter uma melhora na seletividade de reações químicas não somente foi pioneira 8 , mas ele se tornou altamente especializado, um dos maiores conhecedores da funcionalidade analí-tica em compostos orgânicos, conforme o demonstrou no capítulo de mascaramento, no seu livro SSS e igualmente em duas publicações sobre a correlação dos grupamentos atômicos e a afinidade quí-mica 9,10 .…”
Section: Mascaramento E Desmascaramento Em Química -Seletividade Em Qunclassified
“…Vinogradov (20) summarizes the results of analyses of oceanic iodine published up to 1933. In 1932, Evans (6) Prior to the development of the catalytic method for the determination of iodine, no method was sensitive enough to permit a direct determination of the clement in sea water. Iodine was concentrated by precipitation, extraction, or distillation from relatively large samples and final estimation was done either calorimetrically or volumetrically.…”
Section: Determination Of Chemically Combined Iodine In Sea Water By mentioning
confidence: 99%
“…In oxidizing the sample with bromine, the pH of the solution should not be less than about pH 2, as Evans (6) has shown that the reaction is reversible in strongly acid solutions and that elemental iodine is lost when the sample is heated too vigorously to remove excess bromine.…”
Section: Determination Of Total Iodine In Sea Watermentioning
confidence: 99%
“…Et l'on doit, comme le suggère FEIGL [4], se livrer à une investigation systématique, en fonction des conditions qui peuvent changer totalement l'aspect des phénomènes. Cette étude détaillée nous a amené à rechercher les mécanismes responsables des coprécipitations envisagées, même lorsqu'elles ne peuvent être utilisées à des fins analytiques.…”
Section: Introductionunclassified